Identifying indicators of systemic risk - Benny Hartwig; Christoph Meinerding; Yves Schüler (Deutsche Bundesbank, 2020)
We operationalize the definition of systemic risk provided by the IMF, BIS, and FSB and derive testable hypotheses to identify indicators of systemic risk. We map these hypotheses into a two-stage hierarchical testing framework, combining insights from the early-warning literature on financial crises with recent advances on growth-at-risk. Applying this framework to a set of candidate variables, we find that the Basel III credit-to-GDP gap does not indicate systemic risk coherently across G7 countries. Credit growth and house price growth also do not pass our test in many cases. By contrast, a composite financial cycle signals systemic risk consistently for all countries except Canada. Overall, our results suggest that systemic risk may be consistently measured only once the turning points of indicators have been observed. Therefore, pre-emptive countercyclical macroprudential policy may smooth the financial cycle in boom phases, which then indirectly mitigates the amount of systemic risk in the future.
Keywords: E37; E44; G17; 330; systemic risk; macroprudential regulation; forecasting; growth-at-risk; financial cycles